Mapping the Golden Hour: A Spatiotemporal Analysis of Ambulance Response Time in Urban Jakarta - Jailani, Zakiul Fahmi; Nurmadewi, Dita; Syumanjaya, Raden Bambang; Manik, Ni Kadek Sri (GEOSAINS KUTAI BASIN, 2023)
This study aims to map the ambulance response time in Jakarta city and assess the current ambulance to population ratio. The data used in this study include hospital point data retrieved from OpenStreetMap (OSM), manually digitized data points, and a database from community/non-government organizations that manage their own ambulance. The analysis was conducted using a combination of buffer, service area, and overlay tools in GIS (Geo-information System) software. The results show that the current ambulance to population ratio in Jakarta is inadequate, with only 78 ambulances available that can only serve a total population of 5,598,058 out of all 10,748,230 people in Jakarta. This means that at least 215 ambulances are needed to provide comprehensive coverage for the entire population. Furthermore, the golden time for ambulance response, as set by the Ministry of Health in Indonesia, is less than 15 minutes. However, the current ambulance to population ratio in Jakarta makes it difficult to meet this standard.